The long‐term effectiveness of a selective, personality‐targeted prevention program in reducing alcohol use and related harms: a cluster randomized controlled trial. (19th April 2016) - Newton, Nicola C.; Conrod, Patricia J.; Slade, Tim; Carragher, Natacha; Champion, Katrina E.; Barrett, Emma L.; Kelly, Erin V.; Nair, Natasha K.; Stapinski, Lexine; Teesson, Maree
Abstract : Background: This study investigated the long‐term effectiveness of Preventure, a selective personality‐targeted prevention program, in reducing the uptake of alcohol, harmful use of alcohol, and alcohol‐related harms over a 3‐year period. Methods: A cluster randomized controlled trial was conducted to assess the effectiveness of Preventure. Schools were block randomized to one of two groups: the Preventure group ( n  = 7 schools) and the Control group ( n  = 7 schools). Only students screening as high‐risk on one of four personality profiles (anxiety sensitivity, negative thinking, impulsivity, and sensation seeking) were included in the analysis. All students were assessed at five time points over a 3‐year period: baseline; immediately after the intervention; and 12, 24, and 36 months after baseline. Students were assessed on frequency of drinking, binge drinking, and alcohol‐related harms. Two‐part latent growth models were used to analyze intervention effects, which included all students with data available at each time point. This trial is registered with the Australian New Zealand Clinical Trials Registry (ACTRN12612000026820;www.anzctr.org.au ). Results: A total of 438 high‐risk adolescents (mean age, 13.4 years; SD  = 0.47) from 14 Australian schools were recruited to the study and completed baseline assessments. Relative to high‐risk Control students, high‐risk Preventure students displayed significantly reduced growth in their likelihood to consume alcohol [ b  =   −0.225 (0.061); p  <   .001], to binge drink [ b  =   −0.305 (.096); p  =   0.001], and to experience alcohol‐related harms [ b  =   −0.255 (0.096); p  =   .008] over 36 months. Conclusions: Findings from this study support the use of selective personality‐targeted preventive interventions in reducing the uptake of alcohol, alcohol misuse, and related harms over the long term. This trial is the first to demonstrate the effects of a selective alcohol prevention program over a 3‐year period and the first to demonstrate the effects of a selective preventive intervention in Australia.